Low mortality but increasing incidence of Staphylococcus aureus endocarditis in people who inject drugs: Experience from a Swedish referral hospital. Issue 49 (December 2016) - Asgeirsson, Hilmir; Thalme, Anders; Weiland, Ola
Abstract : Abstract: Staphylococcus aureus is a leading cause of infective endocarditis in people who inject drugs (PWID). The management of S aureus endocarditis (SAE) in PWID can be problematic. The objective of this retrospective observational study was to assess the epidemiology, clinical characteristics, and mortality of S aureus endocarditis (SAE) in PWID in Stockholm, Sweden. The Department of Infectious Diseases at the Karolinska University Hospital serves as a regional referral center for drug users with severe infections. Patients with active intravenous drug use treated for SAE at the department between January 2004 and December 2013 were retrospectively identified. Clinical and microbiological data were obtained from medical records and the diagnosis verified according to the modified Duke criteria. In total, 120 SAE episodes related to intravenous drug use were identified. Its incidence in Stockholm was 0.76/100, 000 adult person-years for the entire period, increasing from 0.52/100, 000 person-years in 2004 to 2008 to 0.99 in 2009 to 2013 ( P = 0.02). The SAE incidence among PWID specifically was 249 (range 153–649) /100, 000 person-years. Forty-two (35%) episodes were left-sided, and multiple valves were involved in 26 (22%). Cardiac valve surgery was performed in 10 (8%) episodes, all left-sided. The in-hospital and 1-year mortality rates were 2.5% (3 deaths) and 8.0% (9 deaths), respectively. We noted a high and increasing incidence over time of SAE related to intravenous drug use in Stockholm. The increased incidence partly reflects a rising number of PWID during the study period. The low mortality noted, despite a substantial proportion with left-sided endocarditis, probably in part reflects the quality of care obtained at a large and specialized referral center for drug users with severe infections.